Captured public communication? Private interests, media and necessary regulation in the neoliberal Chile - Jofré Leiva, David; Phillippi, Alejandra (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
Media capture is a concept originally created to understand this industry’s privatization in post-soviet countries. It refers to the process in which media lose autonomy to respond to vested interests instead of playing their informative role. This contribution aims to apply this concept to the Chilean media system, where, despite strict neoliberal guidelines that shaped it during democratization, there is a high level of ownership concentration and a lack of state-led regulation that could prevent corporate capture. This article argues that media capture is an economic dilemma with negative consequences for public communication in Chile, as it restricts journalistic pluralism and suppresses the diversity of ideas and voices necessary for deeper democratic exercises. In front of such a dilemma, the article proposes to reflect on the importance of state-led regulation to mitigate the risks of media capture.